Serum immunoglobulin E levels in children with idiopathic nephrotic syndrome - Ninik Asmaningsih; Windhu Poernomo; M Sjaifullah Noer (Paediatrica Indonesiana, 2005)
Background Children with idiopathic nephrotic syndrome (INS)have been known to have T-cell dysfunction and an impairment ofthe cytokine network that may alter glomerular permeability andthe glomerular filtration barrier. This disorder may contribute to thepresence of urinary protein loss in children with INS. The elevationof serum IgE levels has been noted in some cases, but its associa-tion with steroid-responsive nephrotic syndrome has not been fullyelucidated.Objective This study was done to investigate the association be-tween serum IgE levels prior to prednisone treatment in childrenwith INS and the outcome of treatment.Methods A prospective observational study has been conductedon 22 children with INS. Prednisone therapy was given with a doseof 60 mg/m 2 body surface area (BSA) for four weeks followed by asingle dose of 40 mg/m 2 BSA every other day for another fourweeks. This protocol was applied for steroid-responsive INS chil-dren. Children with steroid resistance were given oral cyclophos-phamide 2 mg/kg for eight weeks. IgE level measurements wereperformed prior to prednisone therapy and at remission. Data wereanalyzed using one-way ANOVA and multiple regression.Results Twenty-two children were enrolled in this study. High lev-els of serum IgE were found in 95.5% of children, with a mean of2002.5 (SD 2172.1) IU/ml. The serum IgE levels of INS childrenwith history of allergy were significantly higher than those of neph-rotic children without history of allergy (P<0.05). However, therewas no significant correlation between the serum IgE levels andthe outcome of treatment in children with INS.Conclusion The high serum IgE levels in children with INS seemto be associated with humoral immune disorder and did not haveany association with the outcome of therapy. Even though the se-rum IgE levels were significantly higher in INS children with historyof allergy, other factors that may influence serum IgE levels mustbe considered